2006
DOI: 10.1016/j.jcat.2006.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn addition to Pt/CeO2–Al2O3 and Pt/Al2O3 catalysts: An XPS, 119Sn Mössbauer and microcalorimetry study

Abstract: The effect of Sn addition to Pt/CeO 2 -Al 2 O 3 and Pt/Al 2 O 3 catalysts was studied with X-ray photoelectron spectroscopy (XPS), 119 Sn Mössbauer spectroscopy and adsorption microcalorimetry of CO at room temperature. Catalysts were reduced in situ at 473 ("non-SMSI state") and 773 K ("SMSI state"). 119 Sn Mössbauer and XPS results indicated that the presence of cerium in bimetallic catalysts inhibited reduction of tin.Furthermore, it was found that tin facilitated reduction of cerium (IV) to cerium (III).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 48 publications
4
58
0
1
Order By: Relevance
“…These values are characteristic of electron transitions in Ni 0 and Ni 2þ , respectively, and are similar to those reported previously [28]. The BE of Pt 4d resides in two regions, at approximately 313.8e314.2 and 317.5e318.7 eV and BE in the regions 314.4e314.5 eV [29] and 317.0e318.0 eV [30] have been determined for Pt 0 and Pt 4þ , respectively. The Pt content measured by XPS was much higher than the Pt content of the bulk material (Table 1).…”
Section: Characterization and Oxi-reduction Properties Of (Xpt(nial)ysupporting
confidence: 89%
“…These values are characteristic of electron transitions in Ni 0 and Ni 2þ , respectively, and are similar to those reported previously [28]. The BE of Pt 4d resides in two regions, at approximately 313.8e314.2 and 317.5e318.7 eV and BE in the regions 314.4e314.5 eV [29] and 317.0e318.0 eV [30] have been determined for Pt 0 and Pt 4þ , respectively. The Pt content measured by XPS was much higher than the Pt content of the bulk material (Table 1).…”
Section: Characterization and Oxi-reduction Properties Of (Xpt(nial)ysupporting
confidence: 89%
“…Generally, the component at lower binding energy ($485.6 eV) corresponds to the reduced Sn species either in zerovalent Sn (Sn 0 ) or in alloyed (SnPt x ) state; while the peaks at $486.5 and $487.4 eV are assigned to oxidized species of Sn. However, it is difficult to discriminate between Sn 2+ and Sn 4+ as their binding energies are very similar [14]. From Table 3, it can be observed that the Sn 0 percentages (26% and 16%) of PtSnIn/0.6Ca-Al and PtSnIn/1.5Ca-Al catalysts are less than that (33%) of PtSnIn/0.0Ca-Al catalyst.…”
Section: Xpsmentioning
confidence: 99%
“…The bimetallic platinum-tin (Pt-Sn) supported catalysts exhibited rather good catalytic performance in propane dehydrogenation [10][11][12][13][14][15][16][17][18][19][20], which had been commercialized by UOP. Since propane dehydrogenation reaction is an endothermic process, it requires a relatively high temperature to obtain high yield of propylene.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Pt4d rather than Pt4f data were analyzed, due to the strong interference caused by the Al2p peak [15,38]. The raw data were deconvoluted into three peaks assigned to Pt 4+ [39][40][41], Pt 2+ [42], and Pt 0 [40]. As shown in Figure 14 and Figure 14.…”
Section: Xps Characterization Of Pt Speciesmentioning
confidence: 99%